The WNT Framework in Shaping Immune Cell Responses During Bacterial Infections - Mukherjee, Tanushree; Balaji, Kithiganahalli Narayanaswamy (Frontiers in Immunology, 2019)
A large proportion of the world is inflicted with health concerns arising from infectious diseases. Moreover, there is a widespread emergence of antibiotic resistance among major infectious agents, partially stemming from their continuous dialog with the host and their enormous capacity to remodel the latter towards a secure niche. Among the several infection-driven events, moderation of WNT signaling pathway has been identified to be strategically tuned during infections to govern host-pathogen interactions. Primarily known for its role in arbitrating early embryonic developmental events; aberrant activation of the WNT pathway has also been associated with immunological consequences during diverse patho-physiological conditions. Here, we review the different mechanisms by which components of WNT signaling pathway are exploited by discrete bacterial agents for their pathogenesis. Furthermore, recent advances on the cross-talk of WNT with other signaling pathways, the varied modes of WNT-mediated alteration of gene expression; and WNT-dependent post-transcriptional and post-translational regulation of the immune landscape during distinct bacterial infections would be highlighted.